Secure map-based crypto-stego technique based on mac address - Kasasbeh, Dima S.; Al-Ja’afreh, Bushra M.; Anbar, Mohammed; Hasbullah, Iznan H.; Al Khasawneh, Mahmoud (Institute of Advanced Engineering and Science, 2024)
Steganography and cryptography are spy craft cousins, working differently to achieve the same target. Cryptography is perceptible and observable without understanding the real content, while steganography hides the content so that it is not perceptible or observable and without producing noticeable changes to the carrier image. The challenge is finding the right balance between security and retrievability of embedded data from embedding locations without increasing the required embedded information. This paper proposes a secure map-based steganography technique to enhance the message security level based on the sender and recipient mac addresses. The proposed technique uses rivest-shamir-adleman (RSA) to encrypt the message, then embeds the cipher message in the host image based on the sender and recipient media access control addresses (mac addresses) exclusive or operation